MENINGKATKAN DISIPLIN DAN TANGGUNG JAWAB SISWA MELALUI SANKSI BERJENJANG PADA SISWA KELAS V SD - Ucok Setia Siregar (Manajer Pendididikan, 2017)
The main objective of this study was to determine the level of discipline and sense of responsibility of students of class V SDN 8. In the first cycle is known that the category of student discipline level value is enough value, the sense of responsibility achieving considerable value, on points chores with a value less. In the second cycle, level of discipline achieving category of very good, the level of responsibility reached very good. An increase in the level of discipline and responsibility of students from the first cycle to cycle to the second because it made improvements on the technique gave the tiered sanctions are varied, with continuous coaching and motivation to the students themselves.